Hard Times for Pacific Nuts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
With world prices for copra and coconut oil at an all time low and many countries in the Pacific heavily subsidizing growers, the coconut industry is facing hard times. To meet the challenge, members of the coconut industry in the region set up the...